Subverting Borders Doing Research on Smuggling and Small-Scale Trade - Bruns, Bettina; Miggelbrink, Judith; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
Small-scale trade and smuggling are part of everyday life at many borders. These trading activities often compensate for economic shortage that many households are suffering from in consequence of e.g. political transformation processes. Despite of the diversity of transborder small-scale trade and smuggling and their wide dispersion, not only in Europe, their reception within social sciences is relatively low. The contributions shed therefore light on research in geography and neighboured disciplines. On the basis of empirical research findings from borders all over the world, the authors thrive to analyse mechanisms and conditions of the informal activities and to detect parallels and differences of informal economic structures from different perspectives. This book is valuable reading for researchers in geography, sociology, ethnography, and in political science.
Keywords: Social sciences; Social Sciences; Sociology, general; Organizational Studies, Economic Sociology